Two-particle azimuthal correlations in ?p interactions using pPb collisions at ?sNN=8.16 TeV - Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Del Valle, A. Escalante; Fruehwirth, R.; Jeitler, M. (Elsevier, 2023)
The first measurements of the Fourier coefficients (V-n Delta) of the azimuthal distributions of charged hadrons emitted from photon-proton (gamma p) interactions are presented. The data are extracted from 68.8nb(-1) of ultra-peripheral proton-lead (pPb) collisions at root s(NN)= 8.16 TeV using the CMS detector. The high energy lead ions produce a flux of photons that can interact with the oncoming proton. This gamma p system provides a set of unique initial conditions with multiplicity lower than in photon-lead collisions but comparable to recent electron-positron and electron-proton data. The V-n Delta coefficients are presented in ranges of event multiplicity and transverse momentum (p(T)) and are compared to corresponding hadronic minimum bias pPb results. For a given multiplicity range, the mean p(T) of charged particles is smaller in gamma p than in pPb collisions. For both the gamma p and pPb samples, V-1 Delta is negative, V-2 Delta is positive, and V-3 Delta consistent with 0. For each multiplicity and p(T) range, V-2 Delta is larger for gamma p events. The gamma p data are consistent with model predictions that have no collective effects. (c) 2023 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/). Funded by SCOAP(3).
Keywords: CMS; Photon-proton; Collectivity